Influence of surface electromyography electrode placement on signal accuracy at forearm muscles during wrist movements - Zadeh, Hossein Ghapanchi (2016)
Surface Electromyography (SEMG) is a technique to detect and monitor the muscles contraction during movements. Applying SEMG signal has difficulties due to complexity nature of this signal. Different type of noise like location of electrodes can affect SEMG signal during data acquisition. Electrode location can significantly important to conquer different type of noises during data collection. There are two ways to overcome this difficulty; 1) finding the best electrode position and 2) finding inter-electrode distance. To find the best electrode location in bipolar recording mode, it was designed and implemented a 6 channel SEMG acquisition system to detect and acquire the upper limb muscles’ SEMG signal. After that, the present study investigated electrode position and inter-electrode distance (IED) for wrist movements over forearm muscles. This study is based on the muscle physiology such as origin, innervation zone (IZ) and tendon zone (TZ) location. Three different electrode positions and three different IED are investigated over thirty volunteers participated during seven daily wrist movements such as wrist extension, flexion, radial deviation, ulnar deviation, wrist rotation and fingers extension and flexion. To find out the best electrode position, the collected signal were analyzed in time and frequency domain. The best electrode location selected where SEMG signal had higher value in time and frequency domain (Mean Absolute Value, Root Mean Square, Power Spectra Density) with lower cross-talk value (Cross-Correlation). The results show a significant differences between various electrode positions in both time and frequency domain. This study recommends the best electrode position over FCR, ECR and ED muscles near muscle origin and IZ with 40mm IED. The best electrode position for ECU and FCU recommend between muscle origin and IZ with 20mm IED. This study also suggests the electrode site for FD muscle is between IZ and TZ with 20mm IED. The presented method should be observed as an important step in every SEMG application and research to guarantee the signal quality.